“Author – Hero – Reader”: Emotional Maxims of the Two Worlds in Anna Gavalda’s 35 Kilos of Hope - Кохан, Роксоляна Андріївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The proposed article deals with the problem of communication within the literary work. The short novel 35 Kilos of Hope by the contemporary French writer Anna Gavalda has been chosen for the analysis. The problem of a child in the adult society through the prism of emotions suggests the extensive material for literary research. Taking into account the principles of receptive poetics, the poetological features of the work have been clarified; its semantic centres have been detected in view of the theory of reader and reading; the detailed analysis of the reception process as the “decoding” of meanings has been conducted from the perspective of emotional formation of the main character (a teenage child).